Voice blogging and L2 speaking performance. Issue 5 (3rd July 2016) - Hsu, Hsiu-Chen
Abstract : This paper reports on an exploratory study that investigated the effect of extensive speaking practice on the development of L2 speaking complexity, accuracy, and fluency in voice blogging. The participants were 30 college EFL (English as a foreign language) learners in Taiwan. As a supplement to the insufficient speaking practice in class, each week over a semester, the participants were required to speak on a topic, record their speaking, and post it onto a class blog outside of class. In addition, they were required to listen to and provide comments on at least one other student's voice blog post every week. Blog posts from the first two and last two weeks were analyzed and compared for complexity (mean number of clauses per AS-unit, mean length of AS-unit, mean length of clause, modified type-token ratio), accuracy (percentage of error-free AS-units, percentage of error-free clauses, percentage of accurate use of grammatical verb forms), and fluency (number of syllables per minute, number of meaningful syllables per minute). Results showed that the participants made an improvement in their speaking complexity (greater mean length of AS-unit and clause) although no such improvement was made in their speaking accuracy and fluency.